DETERMINAN SELF EFFICACY DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN SURAT KABAR HARIAN LAMPUNG POST - Anggalia Wibasuri; Yunada Arpan (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2015)
Self Efficacy needed to encourage employees to believe in his ability in the objectives andexpected results. Self Efficacy high and motivation of employees play a role in improving theperformance of employees. The purpose of this study was to determine the effect of self-efficacy andmotivation to work simultaneously and partially on the performance of employees at the DepartmentEditors Getting Unit Editor and Reporter at PT. Present Mandiri (Daily Lampung). To determine theinfluence of independent variables on the dependent variable partially, t test was used. Whereas todetermine the effect of simultaneous independent variables on the dependent variable used F testsample used in this study were 32 respondents.